MyTalent: Development of Web Based Talent Mapping System for Small and Medium Scale Industry among Graduated Students - Ismail, Mohd Amirul Haziq; Hj Mansor, Marzita (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Tujuan kajian ini adalah untuk membangunkan sistem pemetaan bakat berasaskan web untuk pelajar siswazah yang berminat dalam Industri Kecil dan Sederhana (IKS). Sistem ini dibangunkan sebagai tindak balas kepada kekurangan penyelidikan mengenai penciptaan profil pelajar yang mengambil kira bakat, pengetahuan, dan kemahiran graduan dalam pemilihan pekerjaan. Selain itu, ketiadaan aplikasi atau sistem pemetaan bakat yang boleh membantu pelajar siswazah dalam mengenal pasti kerjaya yang berdaya maju berdasarkan minat, pengetahuan dan kebolehan mereka dalam Industri Kecil dan Sederhana mendorong kajian ini. Metodologi kajian ini adalah berdasarkan Model Prototaip Evolusi (Evolutionary Prototyping Model) yang mempunyai lima fasa. Kajian tinjauan sistem MyTalent menggunakan soal selidik Usefulness, Satisfaction, and Ease (USE). Kaedah pemetaan bakat yang direka bentuk baru ini menjanjikan untuk menyediakan pelajar siswazah baharu dengan perspektif baharu dalam meneroka laluan kerjaya baharu dalam IKS berdasarkan bakal bakat mereka. MyTalent: Development of Web Based Talent Mapping System for Small and Medium Scale Industry among Graduated Students Abstract: The goal of this research is to create a web-based talent mapping system for graduate students interested in small and medium-sized businesses (SMIs). This system was created in response to a lack of research on the development of student profiles that consider graduates' talents, knowledge, and skills when it comes to job selection. Furthermore, the lack of applications or talent mapping systems that can assist graduate students in identifying viable careers in Small and Medium Scale Industries based on their interests, knowledge, and abilities motivates this research. The methodology of this study is based on the five-phase Evolutionary Prototyping Model. The Usefulness, Satisfaction, and Ease (USE) questionnaire was used in the survey study for the MyTalent system. This newly developed talent mapping method promises to give new graduate students a fresh perspective on exploring a new career path in SMIs based on their potential talents. Keywords: Evolutionary Prototyping Model, Talent Mapping System, Web Based.